A Computational Model for Real-Time Calculation of Electric Field due to Transcranial Magnetic Stimulation in Clinics - Alessandra Paffi; Francesca Camera; Filippo Carducci; Gianluigi Rubino; Paolo Tampieri; Micaela Liberti; Francesca Apollonio (International Journal of Antennas and Propagation)
The aim of this paper is to propose an approach for an accurate and fast (real-time) computation of the electric field induced inside the whole brain volume during a transcranial magnetic stimulation (TMS) procedure. The numerical solution implements the admittance method for a discretized realistic brain model derived from Magnetic Resonance Imaging (MRI). Results are in a good agreement with those obtained using commercial codes and require much less computational time. An integration of the developed code with neuronavigation tools will permit real-time evaluation of the stimulated brain regions during the TMS delivery, thus improving the efficacy of clinical applications.